Global monetary economics - Claassen, Emil Maria (Oxford ; New York : Oxford University Press, 1996)
The text covers a complete course in international monetary economics and the treatment of governmental stabilization and adjustment policies to developing countries and transitional economies, as well as analyzing the role of policy in industrialized nations and within monetary unions.
Includes bibliographical references (p. 301-312) and index.
nmn, 20/07/16
Loan
Keywords: International finance; Foreign exchange